FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KONTROL GLIKEMIK PADA PENDERITA DIABETES TIPE 2 - Noorma, Nilam; Prasetyo, Agus; Abidin, M Zainal; Muawanah, Muawanah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Type 2 diabetes mellitus (T2DM) is one of the public health challenges that is gaining serious attention worldwide. Physical activity and acceptance levels are important components in the management of type 2 diabetes mellitus (T2DM) because they play a direct role in controlling blood glucose levels. The purpose of this study was to determine the factors associated with glycemic control in patients with type 2 diabetes. The research design used in this study was cross-sectional. The study was conducted at a community health center in Bandar Lampung in November 2024. The population consisted of all patients diagnosed with type 2 diabetes. The sample size was 130 people. The sampling technique used was probability sampling with purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between physical activity (p value: 0.004) and acceptance level (p value: 0.044) with glycemic control. It is recommended that people with diabetes increase the frequency of physical activity as a step in controlling glycemic levels. Keywords: Physical Activity, Diabetes Mellitus, Acceptance Level